CQC: INFORMAÇÃO E ENTRETENIMENTO NO HUMOR MIDIATIZADO - Silva, Rogério Pereira da (2013)
This dissertation discusses the Humor in the media and their interaction with culture and social imaginary, it is a study of the program Custe o que Custar (CQC), broadcasted by Bandeirantes television network. Describes the evolution of humor in Western history, its relations with the cultures and their foray in the media, in the nineteenth century. Maps the humor present in the Brazilian media in XX and XXI centuries and presents a categorization of television comedy. About television program studied rescued up your history, from its origins in Brazil until today. It has been shown through literature, the process of mediatization of society and the creation of individual and social identities, guided by the production of consumer goods. There was integration among symbolic values of culture, media and social imaginary. We conclude by analyzing the program that humor is an important discursive element in the spread of ideas and values and can be both a transforming element when in accordance with the prevailing social structures. Also, the CQC is one element among many media products, which act as social agents to act in the construction of symbolic values and the social imaginary. In the case studied, the information is confused with entertainment, resulting in a hybrid characteristic of contemporary mediated culture.